Bifunctional Self‐Powered Drug Delivery System to Promote the Release and Transdermal Delivery of Polar Molecules. Issue 14 (10th April 2021) - Ma, Zequn; Zhang, Yi; Zhang, Yihe; An, Qi; Dong, Hong; Fu, Han; Zhang, Hui; Zhang, Shuting; Tong, Wangshu
Abstract: Electrical stimulation to enhance molecular release and transdermal drug delivery has aroused extensive research and clinical medical interest owing to its unique advantages such as being stimuli‐responsive, sensitive, flexible, and controllable. Herein, a self‐powered system driven by piezoelectric substrate is designed to promote the release and transdermal delivery of polar molecules. Notedly, the electric signals generated by piezoelectric substrate contribute to trigger the electric‐responsive drug release and transdermal drug delivery. In addition, the system can be considered as a layer‐by‐layer drug depot with mesoporous silica particles assembled on a piezoelectric flexible composite film, through which the electric signals can be gathered and stored from biomechanical energy. As a result, the ginsenoside Rb1, a representative polar Chinese medicine molecule, can be facilely released from the integrated device in response to finger press. Importantly, the amount of penetration through skin tissues and cells was significantly increased under mechanical stimuli, and the cell bioactivity results manifested that the system also supported high cell viabilities. The integrated device is anticipated to achieving high efficiency in drug release and transdermal delivery via acting as a transdermal patch in the field of biomedicine. Abstract : The article proposed a self‐powered drug delivery system to promote the release and transdermal delivery of Chinese medicine molecules. The system was enabled by assembling the mesoporous silica nanoparticles (MSNPs) layer‐by‐layer multilayers on a piezoelectric film. The integrated device is anticipated to achieve high efficiency in drug release and transdermal delivery via acting as a transdermal patch in the field of biomedicine.